Can clinical characteristics predict the length of hospital stay in vestibular neuritis? - Pina, Paulo (2024)
Objectives: Epidemiological and clinical characterization of the population diagnosed with vestibular neuritis (VN) over a five-year period at a tertiary hospital in Portugal. Evaluate the influence of various characteristics as risk factors for prolonged hospitalization (≥ 8 days). Study design: Retrospective.  Materials and Methods: Review of clinical records of patients hospitalized and treated between January 2019 and December 2023 with a diagnosis of VN. Results: Ninety-nine patients were included. The median age was 62±14.3 years, with 57.6% being women. Only 14.1% had a history of Diabetes Mellitus (DM). The median length of hospital stay was 4±3.3 days. 70.7% of patients presented with grade III nystagmus.  Conclusions: The results suggest, at a statistically significant level, that age ≥ 65 years old (p=0.038), history of DM (p=0.017) and grade of nystagmus at admission (p=0.018) may represent predictive factors for hospitalizations lasting ≥ 8 days in patients with VN.